Peer Effects and Fertility Preferences in China: Evidence from the China Labor-Force Dynamics Survey - Peng Nie; Lu Wang; Alfonso Sousa-Poza (Institute of Labor Economics (IZA), 2020)
Despite empirical evidence that individuals form their fertility preferences by observing social norms and interactions in their environments, the exact impact of these peer effects remains unclear. We thus use data from the 2014 and 2016 China Labor-force Dynamics Survey to investigate the association between community-level peer effects and fertility preferences among Chinese women aged 18-49. Whereas our baseline results indicate that 11.96% of these women would prefer 1 or no children, 74.1% would like 2 children, and 13.93% would prefer 3 or more children. A one unit increase in community-level peer fertility reduces the preference of wanting only one child by 14.3%, whereas it increases the probability of preferring three children by 9.3% and four or more children by 4.8%. Hence, overall, we find a relatively strong peer effect on individual fertility preferences in communities characterized by generally low fertility rates, which provides support for the role of social norms in the fertility choices of reproductive-aged Chinese women.
Keywords: D10; D71; J13; 330; peer effects; fertility; fertility preferences; China